SMART DIGITALIZATION: HOW BANK SULSELBAR TURNS THE PERCEPTION OF CONVENIENCE INTO AN ACTIVE INTEREST OF CREDIT CUSTOMERS - Ghufran Yusuf; Abdul Rahman Kadir; Muhammad Sobarsyah (Program Studi Akuntansi Fakultas Ekonomi dan Bisnis Universitas Kristen Indonesia Paulus, 2023)
The banking sector has been impacted by digital strategies aimed at increasing access to financial services in an era of rapid growth in information technology and internet penetration. Digital strategies require promotions to influence customer perception and interest. This article looks at how Bank Sulselbar uses digital promotional strategies to increase customers' perceived ease and interest in obtaining credit. The use of social media, email marketing, SEO, content marketing, chatbots, webinars, and collaboration with influencers are important steps taken by Bank Sulselbar in an effort to create a good image, increase awareness, and encourage credit taking. This case study collects quantitative data from one hundred respondents. The impact of promotional strategies on customer perceptions of convenience and interest is studied through descriptive and correlation analysis. The research results show that digital promotion strategies are profitable. All things considered, Bank Sulselbar's digital marketing approach was successful in changing people's perceptions of how easy and interesting it is to get credit. Combining these components enables banks to draw in and keep consumers more successfully, enhancing their standing in the competitive banking sector.